High-strength heat-resistant aluminum alloys without heat treatment and their preparation methods
By adding lanthanum and cerium mixed rare earth RE and other elements to the aluminum alloy and using non-equilibrium rapid solidification forming technology to form a nano-scale reinforced phase, the problem of the aluminum alloy's strength decrease under medium/high temperature conditions is solved, and excellent mechanical properties and high temperature stability are achieved.
Patent Information
- Application Number
- CN202411799241.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The strength of existing aluminum alloys has dropped sharply under medium/high temperature conditions, making it difficult to meet the application requirements in high temperature environments.
The alloy design is adopted for mixed rare earth RE, silicon, molybdenum, titanium, chromium and other elements, combined with the unbalanced rapid solidification forming method, the microstructure of the alloy is optimized to form nano-block and/or mesh Al11 (Ce, La) 3 phase.
The excellent mechanical properties of aluminum alloy under room temperature and medium and high temperature conditions are achieved, and its stability and heat resistance under high temperature conditions are improved. The process flow is short and the stability is high, and there is no need for subsequent machining or heat treatment.
Smart Images

Figure CN119242994B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a heat-treatment-free high-strength heat-resistant aluminum alloy and a preparation method thereof. Background Art
[0002] With the rapid development of modern transportation, the requirements for transportation materials are becoming increasingly stringent and diversified. The performance of transportation vehicles such as automobiles, high-speed trains and aircraft directly affects people's travel efficiency and safety. In order to achieve the lightweight of these transportation vehicles, improve their operating efficiency and reduce energy consumption, the application of lightweight aluminum alloy materials has become an effective solution. Lightweight aluminum alloys have been widely used due to their low density, high strength, good processability and good corrosion resistance.
[0003] Lightweight aluminum alloys have many advantages and can meet the requirements of modern transportation for lightweight and high strength, so they are widely used in automobiles, high-speed railways, aircraft and other fields. For example, the use of lightweight aluminum alloy materials can effectively reduce the overall weight of the car, thereby improving fuel efficiency and reducing emissions, while also increasing the speed and operating efficiency of high-speed railways and aircraft.
[0004] However, although lightweight aluminum alloys have excellent performance at room temperature, their performance will be greatly affected under medium / high temperature conditions. Under high temperature conditions, the strength of aluminum alloys will drop sharply as the temperature rises, making it unable to meet the application requirements in high temperature environments. For example, in high temperature environments such as automobile engines, high-speed train braking systems, and aircraft engines, traditional aluminum alloy materials are difficult to meet the requirements of continuous service.
[0005] Therefore, it is necessary to provide a new solution to the problems in the prior art.
[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0007] The object of the present invention is to provide a heat-treatment-free high-strength heat-resistant aluminum alloy and a preparation method thereof, wherein the heat-treatment-free high-strength heat-resistant aluminum alloy has excellent heat resistance and mechanical properties.
[0008] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0009] In a first aspect, the present invention provides a heat-treatment-free high-strength heat-resistant aluminum alloy, which comprises the following components by mass percentage:
[0010] Lanthanum-cerium mixed rare earth RE: 14-16%, silicon: 0.5-1%, molybdenum: 0.2-0.5%, titanium: 0.5-1%, chromium: 0.2-0.5%, and the balance is aluminum and inevitable impurities; wherein the contents of lanthanum and cerium in the lanthanum-cerium mixed rare earth RE are both 30-70%, and the content of other rare earth elements in the lanthanum-cerium mixed rare earth RE is ≤1%.
[0011] In one or more embodiments of the present invention, the total content of molybdenum, titanium and chromium in the heat-treatment-free high-strength and heat-resistant aluminum alloy is 1-1.5%.
[0012] In one or more embodiments of the present invention, the phase composition of the heat-treatment-free high-strength heat-resistant aluminum alloy includes α-Al phase and Al 11 (Ce, La)3 phase.
[0013] In one or more embodiments of the present invention, the Al 11 The (Ce, La)3 phase is distributed on the α-Al phase in the form of nano blocks and / or networks.
[0014] In one or more embodiments of the present invention, the density of the heat-treatment-free high-strength and heat-resistant aluminum alloy is greater than 99%.
[0015] In a second aspect, the present invention provides a method for preparing the aforementioned heat-treatment-free high-strength heat-resistant aluminum alloy, which comprises the following steps:
[0016] Melting and pouring lanthanum-cerium mixed rare earth RE, aluminum and silicon to obtain a cast Al-RE-Si alloy;
[0017] The cast Al-RE-Si alloy is spray-formed and atomized to form Al-RE-Si alloy powder;
[0018] Mixing Al-RE-Si alloy powder, molybdenum powder, titanium powder and chromium powder to obtain mixed powder;
[0019] The mixed powder is melt-formed by non-equilibrium rapid solidification forming method to obtain a high-strength and heat-resistant aluminum alloy without heat treatment.
[0020] In one or more embodiments of the present invention, the atomization temperature of the spray forming is 800-900° C., the atomization pressure is 5-10 MPa, and the atomization distance is 600-1000 mm.
[0021] In one or more embodiments of the present invention, the particle size distribution of the Al-RE-Si alloy powder is between 15 and 65 μm, and the average particle size is between 45 and 55 μm.
[0022] In one or more embodiments of the present invention, a non-equilibrium rapid solidification molding method is used to melt-form the mixed powder, specifically: a laser powder bed is used to melt-form the mixed powder.
[0023] In one or more embodiments of the present invention, the printing power of the laser powder bed is 220-300 W, the scanning rate is 800-1200 mm / s, and the laser volume energy density is 60-100 J / mm 3 .
[0024] Compared with the prior art, the heat-treatment-free high-strength and heat-resistant aluminum alloy provided by the present invention is formed by a specific alloy element design combined with a non-equilibrium rapid solidification forming method to optimize the microstructure of the alloy, thereby achieving excellent mechanical properties of the aluminum alloy at room temperature and medium and high temperature conditions; and the heat-treatment-free high-strength and heat-resistant aluminum alloy can be directly printed and formed, with a short process flow, high stability, and near-net forming. No subsequent machining or heat treatment is required, and it can be used to produce heat-resistant aluminum alloy components with complex shapes, such as internal combustion engine cylinders, high-horsepower engine pistons, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the TEM morphology of the heat-treatment-free high-strength and heat-resistant aluminum alloy prepared in Example 1 at room temperature. DETAILED DESCRIPTION
[0026] The specific implementation modes of the present invention are described in detail below in conjunction with the embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.
[0027] It should be noted that in the following description, the "%" indicating the amount is a weight basis unless otherwise specified. Unless otherwise specified, all numbers used in this specification and claims to indicate characteristic dimensions, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0028] It should also be noted that the terms "include", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus; the term "preferred" refers to a better option, but is not limited to the selected option.
[0029] Although existing aluminum alloys have good light weight and high strength properties at room temperature, their mechanical properties will significantly decrease under medium / high temperature conditions, making it difficult for them to continue to serve in high temperature environments. This is mainly because the strengthening phase contained in the existing aluminum alloys will dissolve, grow and copolymerize at high temperatures, losing its strengthening effect, and also affecting the thermal stability and oxidation resistance of the aluminum alloy.
[0030] In view of the problems existing in the existing aluminum alloys, the present invention provides a new high-strength and heat-resistant aluminum alloy without heat treatment and a preparation method thereof. The core of the technical realization idea of the present invention is to optimize the microstructure of the alloy by designing specific alloy elements and combining the non-equilibrium rapid solidification molding method, so as to achieve excellent mechanical properties of the aluminum alloy at room temperature and medium and high temperature conditions, and improve its stability and heat resistance under high temperature conditions.
[0031] The heat-treatment-free high-strength and heat-resistant aluminum alloy provided in one embodiment of the present invention comprises the following components by mass percentage: lanthanum-cerium mixed rare earth RE: 14-16%, silicon: 0.5-1%, molybdenum: 0.2-0.5%, titanium: 0.5-1%, chromium: 0.2-0.5%, and the balance is aluminum and unavoidable impurities; wherein the contents of lanthanum and cerium in the lanthanum-cerium mixed rare earth RE are both 30-70%, and the contents of other rare earth elements in the lanthanum-cerium mixed rare earth RE are ≤1%. The preparation method of the heat-treatment-free high-strength and heat-resistant aluminum alloy comprises: preparing Al-RE-Si alloy powder by a spray deposition gas atomization powder making process, mixing the Al-RE-Si alloy powder with molybdenum powder, titanium powder, and chromium powder, and then forming the powder by a non-equilibrium rapid solidification molding method.
[0032] In this embodiment, the low-cost rare earth mining byproduct lanthanum-cerium mixed rare earth is used as the main alloy element, which can avoid the use of expensive and scarce single rare earth elements, reduce costs and resource consumption, and effectively improve the thermal stability and oxidation resistance of the aluminum alloy.
[0033] It should be noted that lanthanum (La) and cerium (Ce) are two common rare earth elements. They have large atomic radius and high electronegativity and can form Al 11 (Ce, La)3 phase. Al 11The (Ce, La)3 phase has a high melting point, hardness and stability, and can exist in the aluminum matrix as a strengthening phase, thereby improving the mechanical properties of the aluminum alloy.
[0034] Lanthanum and cerium can promote the non-equilibrium eutectic reaction and form a grid-like Al2O3 in the aluminum matrix that is coherent with the matrix. 11 (Ce, La)3 phase. This grid-like strengthening phase has high strength and hardness, and can effectively prevent dislocation movement and slip, thereby improving the room temperature and high temperature strength of aluminum alloys.
[0035] Lanthanum and cerium can form composite strengthening phases with other transition elements (such as Mo, Ti, Cr, etc.), such as Al 11 (Ce, La)3-Mo、Al 11 (Ce, La)3-Ti and Al 11 (Ce, La)3-Cr, etc. These composite strengthening phases have higher melting points and lower diffusion rates, which can maintain their strengthening effects under high temperature conditions, and can also improve the heat resistance and oxidation resistance of aluminum alloys.
[0036] Lanthanum and cerium can inhibit grain growth, refine grains, and increase grain boundary area, thereby enhancing the creep resistance and fatigue resistance of aluminum alloys. Fine grains can hinder grain boundary diffusion, reduce grain boundary sliding, and increase grain boundary strength.
[0037] Lanthanum and cerium can improve the plasticity and toughness of aluminum alloys, enhance their deformation coordination ability, reduce the solution temperature and solution time of aluminum alloys, reduce residual stress, increase plastic deformation, and promote the precipitation of fine equiaxed aluminum matrix structure in the matrix to improve its ductility.
[0038] The spray deposition gas atomization powder making process is to quickly spray the molten Al-RE-Si alloy to form tiny droplets, and solidify them into powder at a high cooling rate. In this process, the Al-RE-Si alloy formed by mixing rare earth elements lanthanum (La) and cerium (Ce) with aluminum and silicon can form a uniform microstructure through rapid cooling. Rapid cooling can not only avoid the segregation of alloy components, but also refine the grains and form phases with high thermal stability, such as Al 11 (Ce, La)3 phase. The presence of this phase can improve the high temperature strength and heat resistance of the alloy.
[0039] The mixing step is to evenly mix the prepared Al-RE-Si alloy powder with molybdenum, titanium and chromium powder. Molybdenum, titanium and chromium are transition metal elements that can significantly improve the mechanical properties and heat resistance of the alloy through various mechanisms such as solid solution strengthening, precipitation strengthening and grain refinement. For example, molybdenum has a high melting point and low diffusion rate, which can inhibit the growth of grains and enhance the creep resistance of the material; titanium and chromium can further optimize the alloy performance by refining the grain structure and forming a stable phase. By evenly mixing, it is ensured that these elements are evenly distributed in the subsequent molding process to avoid inconsistent performance.
[0040] Non-equilibrium rapid solidification molding is the core step of this process, which realizes the molding of materials by rapid melting and rapid cooling. Under high cooling rate, Al-RE-Si alloy powder and its components mixed with molybdenum, titanium and chromium can form nano-scale strengthening phase and uniform microstructure. This method can avoid the segregation and coarse grain problems that may occur in traditional casting process.
[0041] In this embodiment, the mass content of the lanthanum-cerium mixed rare earth RE is set to 14-16%, for example, it can be 14%, 14.3%, 14.5%, 15%, 15.6%, 16%, etc. Among them, the content of lanthanum and cerium in the lanthanum-cerium mixed rare earth RE is ≥30% (that is, the content of lanthanum in the lanthanum-cerium mixed rare earth RE is 30-70%, and the content of cerium is 30-70%), and the content of the remaining rare earth elements (such as neodymium, samarium, neodymium, etc.) in the lanthanum-cerium mixed rare earth RE except lanthanum and cerium is ≤1%.
[0042] When the mass content of lanthanum-cerium mixed rare earth RE is 14-16%, more grid-like Al 11 (Ce, La)3 phase, thus achieving a better strengthening effect. If the mass content of lanthanum-cerium mixed rare earth RE is less than 14%, the grid-like Al 11 The amount and distribution of (Ce, La)3 phase are not sufficient to effectively prevent dislocation movement and slip, thereby reducing the strength of aluminum alloy. If the mass content of lanthanum-cerium mixed rare earth RE is higher than 16%, the grid-like Al 11 Excessive amount and distribution of (Ce, La)3 phase will cause the aluminum matrix to be too brittle, thereby reducing the plasticity and toughness of the aluminum alloy.
[0043] When the contents of lanthanum and cerium in the lanthanum-cerium mixed rare earth RE are both 30-70%, the synergistic effect of the two elements in the alloy can be ensured to ensure Al 11 The formation and stability of (Ce, La)3 phase can improve the heat resistance and oxidation resistance of aluminum alloy. If the content of lanthanum or cerium in the lanthanum-cerium mixed rare earth RE is less than 30%, then Al 11The (Ce, La)3 phase will partially dissolve or transform into other phases with lower melting point, lower strength and lower stability, such as Al2(Ce, La) or Al3(Ce, La) phase, thereby reducing the high temperature performance of aluminum alloy.
[0044] When the content of other rare earth elements in the lanthanum-cerium mixed rare earth RE is greater than 1%, the influence of impurity elements on the matrix and strengthening phase may increase, such as forming a brittle phase, increasing grain size, reducing grain boundary strength, etc., thereby reducing the comprehensive performance of the aluminum alloy.
[0045] It should also be noted that molybdenum (Mo), titanium (Ti), and chromium (Cr) are transition metal elements, and their addition can improve the mechanical properties of aluminum alloys at medium and high temperatures. Mo, Ti, and Cr elements can form solid solutions and precipitation phases in the aluminum matrix. In the solid solution, their atoms will be embedded in the aluminum lattice, causing lattice distortion and hindering the movement of dislocations, thereby improving the strength and hardness of the material. Under appropriate conditions, they can also precipitate to form hard phases, further enhancing the strength and heat resistance of the alloy.
[0046] Mo, Ti and Cr elements can act as grain refiners to promote grain refinement of aluminum alloys. The refined grain structure can provide more grain boundaries, block the movement of dislocations, and enhance the strength of the material. At the same time, fine grains help resist grain growth and recrystallization at high temperatures and maintain the microstructural stability of the alloy.
[0047] Mo, Ti and Cr elements all have good anti-oxidation and anti-corrosion properties. They can form a tight oxide layer on the surface of the alloy to protect the alloy from high-temperature oxidation and corrosion, thereby maintaining its performance under high-temperature conditions.
[0048] The addition of Mo, Ti and Cr can increase the growth restriction factor of the melt by slowing down the diffusion rate of solute elements in the aluminum matrix. This helps to inhibit the growth of aluminum matrix grains, further refine the grain structure, and improve the high temperature properties of the alloy.
[0049] Mo, Ti and Cr have a synergistic effect with other alloying elements, such as lanthanum and cerium. They form new alloy phases with lanthanum and cerium, such as Al 11 (Ce, La)3-Mo、Al 11 (Ce, La)3-Ti and Al 11 (Ce, La)3-Cr, etc., further enhance the strength and heat resistance of the alloy.
[0050] In this embodiment, the content of molybdenum in the heat-treatment-free high-strength heat-resistant aluminum alloy is 0.2-0.5%, the content of titanium is 0.5-1%, and the content of chromium is 0.2-0.5%. Among them, the total content of molybdenum, titanium and chromium in the heat-treatment-free high-strength heat-resistant aluminum alloy is preferably 1-1.5%, for example, it can be 1%, 1.1%, 1.25%, 1.3%, 1.4%, 1.5%, etc.
[0051] The content of molybdenum is limited to 0.2~0.5%, which can improve the high temperature strength and heat resistance of aluminum alloy, and can also form a composite strengthening phase Al with lanthanum-cerium mixed rare earth. 11 (Ce, La)3-Mo. If the content of molybdenum is less than 0.2%, it is not conducive to Al 11 The formation of (Ce, La)3-Mo. If the content of molybdenum is higher than 0.5%, it will increase the density and rigidity of the aluminum alloy and reduce the lightness and plasticity of the aluminum alloy.
[0052] The titanium content is limited to 0.5~1%, which can improve the high temperature strength and heat resistance of aluminum alloys, and can also form a composite strengthening phase Al with lanthanum-cerium mixed rare earth. 11 (Ce, La)3-Ti. If the titanium content is less than 0.5%, it is not conducive to Al 11 The formation of (Ce,La)3-Ti. If the titanium content is higher than 1%, it will increase the rigidity and brittleness of the aluminum alloy and reduce the plasticity and toughness of the aluminum alloy.
[0053] The content of chromium is 0.2~0.5%. Chromium can improve the heat resistance and oxidation resistance of aluminum alloy, and can also form a composite strengthening phase Al with lanthanum-cerium mixed rare earth. 11 (Ce, La)3-Cr. If the chromium content is less than 0.2%, it is not conducive to Al 11 The formation of (Ce,La)3-Cr. If the chromium content is higher than 0.5%, it will increase the brittleness and welding crack tendency of the aluminum alloy and reduce the toughness and welding performance of the aluminum alloy.
[0054] Furthermore, limiting the total content of molybdenum, titanium and chromium to 1~1.5% can ensure that while meeting the requirements of aluminum alloy such as strength, heat resistance and oxidation resistance, factors such as cost, density, stiffness, plasticity, toughness and weldability are also taken into consideration, so that the aluminum alloy has excellent comprehensive performance.
[0055] In an exemplary embodiment, the phase composition of the heat-treatment-free high-strength heat-resistant aluminum alloy includes α-Al phase and Al 11 (Ce,La)3 phase, Al 11 The (Ce, La)3 phase is distributed on the α-Al phase in the form of nano-blocks and / or networks. 11The (Ce, La)3 phase provides strength and heat resistance, while the α-Al matrix phase provides ductility and coordinates deformation.
[0056] Al 11 The (Ce, La)3 phase is an intermetallic compound coherent with the matrix, with a high melting point (about 1200°C), high hardness (about 8.5 GPa) and high stability. This strengthening phase can effectively prevent dislocation movement and slip, thereby improving the room temperature and high temperature strength of the aluminum alloy. At the same time, this strengthening phase also has good heat resistance and oxidation resistance, and can maintain its morphology and distribution under high temperature conditions, thereby ensuring the long-term service performance of the aluminum alloy.
[0057] Al 11 The (Ce, La)3 phase is distributed in the form of nano-blocks and / or networks on the α-Al phase. This distribution method can form an effective load transfer and constraint effect between the strengthening phase and the matrix, thereby enhancing the creep resistance and fatigue resistance of the aluminum alloy. At the same time, this distribution method can also avoid the problem of excessive brittleness or fracture of the matrix due to excessive or large strengthening phases.
[0058] The α-Al matrix has a solid solution with good plasticity and toughness, which can provide ductility and coordinate deformation of aluminum alloy. The α-Al matrix contains a small amount of lanthanum, cerium, molybdenum, titanium, chromium and other elements, which can inhibit grain growth, refine grains, increase grain boundary area, and thus enhance the creep resistance and fatigue resistance of aluminum alloy. At the same time, these elements can also react with Al 11 (Ce, La)3 phase forms a composite strengthening phase, such as Al 11 (Ce, La)3-Mo、Al 11 (Ce, La)3-Ti and Al 11 (Ce, La)3-Cr, etc., further improve the high temperature strength and heat resistance of aluminum alloys.
[0059] In an exemplary embodiment, the density of the heat-treatment-free high-strength and heat-resistant aluminum alloy is greater than 99%.
[0060] It should be noted that the density of the heat-treatment-free high-strength heat-resistant aluminum alloy refers to the ratio of the actual density of the aluminum alloy to the theoretical density, which reflects the amount and distribution of pores in the aluminum alloy. The higher the density, the fewer pores in the aluminum alloy, the more uniform the structure, and the better the performance. The lower the density, the more pores in the aluminum alloy, the more uneven the structure, and the worse the performance.
[0061] Since heat-treatment-free high-strength heat-resistant aluminum alloy contains a variety of alloying elements and strengthening phases, if the density is not high enough, it may lead to uneven distribution of these elements and phases, resulting in inconsistency in structure and performance. For example, if La, Ce, Mo, Ti, Cr and other elements are unevenly distributed in the aluminum matrix, it will affect the Al11 The formation and stability of (Ce, La)3 phase can be affected, thereby reducing the strength and heat resistance of aluminum alloys.
[0062] Porosity in heat-resistant aluminum alloys without heat treatment will reduce the mechanical properties and stability of aluminum alloys and increase their brittleness and sensitivity. For example, pores will reduce the tensile strength, yield strength, fracture toughness, creep resistance, fatigue resistance, etc. of aluminum alloys. Porosity will also increase stress concentration, crack propagation, hydrogen embrittlement, stress corrosion, etc. of aluminum alloys.
[0063] The pores in the heat-resistant aluminum alloy without heat treatment will also affect the physical properties of the aluminum alloy, such as electrical conductivity, thermal conductivity, magnetism, and optics. For example, the pores will reduce the resistivity, thermal conductivity, and reflectivity of the aluminum alloy. The pores will also affect the surface quality, paintability, weldability, and other process properties of the aluminum alloy.
[0064] In one embodiment of the present invention, a method for preparing the aforementioned heat-treatment-free high-strength heat-resistant aluminum alloy is further provided, and the method specifically comprises the following steps:
[0065] S101: Melt and pour lanthanum-cerium mixed rare earth RE, aluminum and silicon to obtain a cast Al-RE-Si alloy.
[0066] It should be noted that appropriate raw materials can be selected according to the design composition of the aluminum alloy, such as pure aluminum ingots, lanthanum-cerium mixed rare earth RE, silicon ingots, etc. Lanthanum-cerium mixed rare earth RE can use low-cost rare earth mining byproducts, such as chlorides or oxides containing more than 30% lanthanum and cerium.
[0067] In order to prevent aluminum alloy from oxidation, hydrogen absorption, inclusions, etc. during the melting process, inert gas or vacuum should be used as the melting atmosphere. The inert gas can be nitrogen, argon or a mixed gas, and its flow rate and pressure should be adjusted according to the furnace type and the size of the molten pool to keep the molten pool surface calm and clean.
[0068] In order to ensure the complete melting and uniform mixing of the aluminum alloy, and also to avoid overheating and burning of the aluminum alloy caused by excessively high temperature, an appropriate melting temperature should be used. Generally speaking, the melting temperature should be about 50~100℃ higher than the liquidus temperature of the aluminum alloy.
[0069] S102: spray-forming the cast Al-RE-Si alloy and atomizing it to form Al-RE-Si alloy powder.
[0070] It should be noted that in step S102 , the atomization temperature of the spray molding is preferably 800-900° C., the atomization pressure is preferably 5-10 MPa, and the atomization distance is preferably 600-1000 mm.
[0071] Atomization temperature refers to the temperature at which the cast Al-RE-Si alloy is heated to a liquid or semi-liquid state for spray forming. The atomization temperature should be about 50~100 ℃ higher than the liquidus temperature of the aluminum alloy to ensure complete melting and fluidity of the aluminum alloy. If the atomization temperature is too low, it will cause partial solid phase or overcooling of the aluminum alloy, affecting its atomization effect and uniformity. If the atomization temperature is too high, it will cause overheating and burning of the aluminum alloy, affecting its structure and performance.
[0072] Atomization pressure refers to the inert gas pressure applied to liquid or semi-liquid aluminum alloy through the nozzle to atomize it into fine droplets. The atomization pressure should be adjusted according to factors such as the structure and size of the nozzle, the fluidity and viscosity of the aluminum alloy, etc. to ensure good atomization effect and uniformity of the aluminum alloy. If the atomization pressure is too low, the droplets of the aluminum alloy will be too large or irregular, affecting its flight and cooling process. If the atomization pressure is too high, the droplets of the aluminum alloy will be too small or too dispersed, affecting its deposition and forming effect.
[0073] The atomization distance refers to the distance from the nozzle to the substrate or collector, which affects the state and changes of the aluminum alloy droplets during flight and cooling. The atomization distance should be determined based on factors such as the injection speed, cooling rate, and solid phase ratio to ensure that the aluminum alloy droplets reach the required temperature and structure before reaching the substrate or collector. If the atomization distance is too short, the aluminum alloy droplets will not be fully cooled and solidified, affecting their deposition and forming effects. If the atomization distance is too long, the aluminum alloy droplets will be overcooled and solidified, affecting their adhesion and density.
[0074] Preferably, the particle size distribution of the Al-RE-Si alloy powder is between 15 and 65 μm, the average particle size is 45 to 55 μm, and the sphericity of the Al-RE-Si alloy powder is greater than or equal to 95%.
[0075] S103: Al-RE-Si alloy powder, molybdenum powder, titanium powder and chromium powder are mixed to obtain mixed powder.
[0076] In step S103, the equipment used to achieve mixing can be one or more combinations of crushing and dispersing equipment such as a double-roll crusher, an ultrafine stone mill, a magnetic stirrer, a mechanical stirrer, a nanoparticle disperser, a coating machine, a wet sand mill, a pulverizer, a planetary ball mill, a VC mixer, a centrifugal ball mill, etc.
[0077] S104: The mixed powder is melt-formed by non-equilibrium rapid solidification forming method to obtain a high-strength and heat-resistant aluminum alloy without heat treatment.
[0078] It should be noted that the non-equilibrium rapid solidification molding method refers to the use of high-energy-density heat sources, such as lasers and electron beams, to locally melt and rapidly solidify the mixed powder, thereby preparing aluminum alloys of the desired shape and size. The non-equilibrium rapid solidification molding method can use non-equilibrium eutectic reactions to generate a grid-like Al 11 (Ce, La)3 phase, and its morphology and distribution can be controlled to make it evenly distributed in a fine equiaxed aluminum matrix. At the same time, molybdenum, titanium and chromium elements can also be combined with Al 11 (Ce, La)3 phase forms a composite strengthening phase, such as Al 11 (Ce, La)3-Mo、Al 11 (Ce, La)3-Ti and Al 11 (Ce, La)3-Cr, etc.
[0079] Specifically, a laser powder bed can be used to melt the mixed powder, wherein the printing power of the laser powder bed is preferably 220-300 W, the scanning rate is preferably 800-1200 mm / s, and the laser volume energy density is preferably 60-100 J / mm 3 .
[0080] The laser powder bed fusion molding process is a non-equilibrium rapid solidification molding method. It uses a laser beam as a heat source to scan and melt the mixed powder on the powder bed layer by layer, thereby depositing the required shape and size of aluminum alloy layer by layer. The printing parameters of the laser powder bed refer to various factors that affect the interaction between the laser and the mixed powder, such as printing power, scanning rate, laser volume energy density, etc.
[0081] The printing power should be moderate so that the mixed powder can be completely melted and form a good molten pool. If the printing power is too low, the mixed powder will be partially solid or overcooled, affecting its melting effect and uniformity. If the printing power is too high, the mixed powder will be overheated and burned, affecting its structure and performance.
[0082] The scanning rate should be moderate so that the mixed powder can be fully mixed and quickly solidified in the molten pool. If the scanning rate is too low, the mixed powder will stay in the molten pool for too long, affecting its cooling rate and solid phase ratio. If the scanning rate is too high, the mixed powder will stay in the molten pool for too short a time, affecting its mixing effect and consistency.
[0083] The laser volume energy density should be appropriate so that the mixed powder reaches the required temperature and structure. The laser volume energy density refers to the laser energy input into the mixed powder per unit volume, which is related to parameters such as printing power, scanning rate, scanning spacing, layer thickness, etc. If the laser volume energy density is too low, the mixed powder will not be fully melted and homogenized, affecting its deposition and molding effect. If the laser volume energy density is too high, the mixed powder will be overcooled and solidified, affecting its bonding and density.
[0084] The present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0085] Example 1
[0086] The chemical composition of the heat-treatment-free high-strength heat-resistant aluminum alloy is: 15% of lanthanum-cerium mixed rare earth RE; 0.7% of Si; 0.3% of Mo; 0.5% of Ti; 0.4% of Cr; the remainder is Al and unavoidable impurities. Among them, Ce in the lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0087] Preparation process:
[0088] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0089] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0090] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 850°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 48μm, and a sphericity of 98%.
[0091] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0092] The mixed powder is melted and formed by laser powder bed to obtain high-strength and heat-resistant aluminum alloy without heat treatment. The process parameters of laser powder bed are: printing power is 250W, scanning speed is 1000mm / s, laser volume energy density is 80J / mm 3 .
[0093] Figure 1This is the TEM morphology of the heat-treatment-free high-strength and heat-resistant aluminum alloy prepared in Example 1 at room temperature.
[0094] Example 2
[0095] The chemical composition of the heat-treatment-free high-strength heat-resistant aluminum alloy is: lanthanum-cerium mixed rare earth RE: 16%; Si: 1.0%; Mo: 0.5%; Ti: 0.8%, Cr: 0.2%, and the balance is Al and unavoidable impurities. Among them, Ce in the lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0096] Preparation process:
[0097] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0098] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0099] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 850°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 50μm, and a sphericity of 98%.
[0100] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0101] The mixed powder is melted and formed by laser powder bed to obtain high-strength and heat-resistant aluminum alloy without heat treatment. The process parameters of laser powder bed are: printing power is 250W, scanning speed is 1000mm / s, laser volume energy density is 80J / mm 3 .
[0102] Example 3
[0103] The chemical composition of the heat-treatment-free high-strength heat-resistant aluminum alloy is: 14% of lanthanum-cerium mixed rare earth RE; 0.7% of Si; 0.3% of Mo; 0.5% of Ti; 0.4% of Cr; the remainder is Al and unavoidable impurities. Among them, Ce in the lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0104] Preparation process:
[0105] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0106] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0107] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 900°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 51μm, and a sphericity of 98%.
[0108] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0109] The mixed powder is melted and formed by laser powder bed to obtain high-strength and heat-resistant aluminum alloy without heat treatment. The process parameters of laser powder bed are: printing power is 250W, scanning speed is 1000mm / s, laser volume energy density is 80J / mm 3 .
[0110] Example 4
[0111] The chemical composition of the heat-treatment-free high-strength heat-resistant aluminum alloy is: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, and the balance is Al and unavoidable impurities. Among them, Ce in RE accounts for 69.3% of the total amount of mixed rare earth, La accounts for 30.3% of the total amount of mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0112] Preparation process:
[0113] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0114] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0115] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 850°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 48μm, and a sphericity of 98%.
[0116] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0117] The mixed powder is melted and formed by laser powder bed to obtain high-strength and heat-resistant aluminum alloy without heat treatment. The process parameters of laser powder bed are: printing power of 280W, scanning speed of 800mm / s, laser volume energy density of 90J / mm 3 .
[0118] Example 5
[0119] The chemical composition of the heat-treatment-free high-strength heat-resistant aluminum alloy is: 15% of lanthanum-cerium mixed rare earth RE; 0.7% of Si; 0.3% of Mo; 0.5% of Ti; 0.4% of Cr; the remainder is Al and unavoidable impurities. Among them, Ce in the lanthanum-cerium mixed rare earth RE accounts for 40.4% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 59.1% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.5%.
[0120] The preparation process is the same as that in Example 1.
[0121] Example 6
[0122] The chemical composition of the heat-treatment-free high-strength heat-resistant aluminum alloy is: 15% of lanthanum-cerium mixed rare earth RE; 0.7% of Si; 0.3% of Mo; 0.5% of Ti; 0.4% of Cr; the remainder is Al and unavoidable impurities. Among them, Ce in the lanthanum-cerium mixed rare earth RE accounts for 30.2% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 69.5% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.3%.
[0123] The preparation process is the same as that in Example 1.
[0124] Example 7
[0125] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0126] Preparation process:
[0127] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0128] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0129] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 850°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 48μm, and a sphericity of 98%.
[0130] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0131] The mixed powder was subjected to laser cladding forming to obtain aluminum alloy, wherein the laser power was 1600 W, the scanning rate was 600 mm / min, the layer thickness was 0.5 mm, and the scanning spacing was 1.2 mm.
[0132] Comparative Example 1
[0133] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 10%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0134] The preparation process is the same as that in Example 1.
[0135] Comparative Example 2
[0136] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 13%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0137] The preparation process is the same as that in Example 1.
[0138] Comparative Example 3
[0139] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 17%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0140] The preparation process is the same as that in Example 1.
[0141] Comparative Example 4
[0142] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 20.5% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 79.1% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0143] The preparation process is the same as that in Example 1.
[0144] Comparative Example 5
[0145] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 76.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 23.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0146] The preparation process is the same as that in Example 1.
[0147] Comparative Example 6
[0148] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.7%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0149] The preparation process is the same as that in Example 1.
[0150] Comparative Example 7
[0151] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 1.1%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0152] The preparation process is the same as that in Example 1.
[0153] Comparative Example 8
[0154] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.8%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0155] The preparation process is the same as that in Example 1.
[0156] Comparative Example 9
[0157] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.1%; Ti: 0.5%, Cr: 0.3%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0158] The preparation process is the same as that in Example 1.
[0159] Comparative Example 10
[0160] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.2%; Ti: 0.4%, Cr: 0.3%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0161] The preparation process is the same as that in Example 1.
[0162] Comparative Example 11
[0163] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.1%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0164] The preparation process is the same as that in Example 1.
[0165] Comparative Example 12
[0166] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0167] Preparation process:
[0168] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0169] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0170] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 850°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 48μm, and a sphericity of 98%.
[0171] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0172] The mixed powder is hot pressed to obtain aluminum alloy. The hot pressing process parameters are as follows: hot pressing pressure is 35 MPa, holding time is 50 min, vacuum degree is about 1.0×10 -2 Pa.
[0173] Comparative Example 13
[0174] The chemical composition of aluminum alloy: lanthanum-cerium mixed rare earth RE: 15%; Si: 0.7%; Mo: 0.3%; Ti: 0.5%, Cr: 0.4%, the balance is Al and unavoidable impurities. Among them, Ce in lanthanum-cerium mixed rare earth RE accounts for 69.3% of the total amount of lanthanum-cerium mixed rare earth, La accounts for 30.3% of the total amount of lanthanum-cerium mixed rare earth, and the total amount of other rare earth elements is less than 0.4%.
[0175] Preparation process:
[0176] Calculate the required amount of raw materials according to the chemical composition and stoichiometric ratio of the alloy.
[0177] In a protective atmosphere, lanthanum-cerium mixed rare earth RE, pure aluminum ingot and silicon ingot are heated to 850° C. for melting, and after degassing and deslagging, a cast Al-RE-Si alloy is obtained by pouring.
[0178] The cast Al-RE-Si alloy was placed in a spray forming induction furnace for spray forming, wherein the process parameters of the spray forming were: atomization temperature of 850°C, atomization pressure of 8MPa, and atomization distance of 1000mm. After the alloy powder was collected, the alloy powder was screened to obtain Al-RE-Si alloy powder with a particle size distribution of 15-65μm, an average particle size of 48μm, and a sphericity of 98%.
[0179] The Al-RE-Si alloy powder, pure Mo powder, pure Ti powder and pure Cr powder are ball-milled and mixed in a ball mill at a ball-milling speed of 1000 r / min and a ball-milling time of 30 min to obtain a mixed powder.
[0180] The mixed powder is subjected to spark plasma sintering to obtain an aluminum alloy. The mold material used in the sintering process is high-strength graphite, the sintering temperature is 525°C, the heating rate is 75°C / min, the holding time is 6min, and the sintering pressure is 50MPa.
[0181] According to the relevant standards GB / T228.1-2010 and GB / T 228.2-2015, the room temperature tensile strength and 350°C tensile strength of the aluminum alloys prepared in the embodiments and comparative examples were tested. The test results are shown in Table 1 below:
[0182] Table 1 - Aluminum alloy tensile strength test results
[0183]
[0184] According to Table 1 and Examples 1 to 6, the heat-treatment-free high-strength heat-resistant aluminum alloy provided by the present invention has excellent mechanical properties at room temperature and medium / high temperatures. This is because the content of the lanthanum-cerium mixed RE in the present invention is calculated based on the nucleation work theory and the LKT / BCT rapid solidification dendrite growth model. When the content of La and Ce is greater than the eutectic composition at a critical cooling rate and a large degree of supercooling, a hypoeutectic coherent continuous network distribution Al with good comprehensive mechanical properties can be obtained. 11 (Ce, La)3 phase. The contents of Mo, Ti, and Cr are calculated based on the limiting growth factor. The trace addition of elements with high melting points and slow diffusion rates significantly increases the limiting growth factor, increases the supercooling under rapid solidification conditions, inhibits grain growth, and promotes the transformation of columnar crystals to equiaxed crystals, so that a higher content of equiaxed α-Al phase is obtained in the aluminum matrix.
[0185] According to Table 1 in combination with Example 1 and Comparative Examples 1 to 5, if the content of lanthanum-cerium mixed rare earth RE or the content of La and Ce in lanthanum-cerium mixed rare earth RE is too high or too low, the mechanical properties of the aluminum alloy will be significantly deteriorated.
[0186] According to Table 1 in combination with Example 1 and Comparative Examples 6 to 11, it can be seen that excessively high or low contents of Mo, Ti, and Cr will lead to significant deterioration of the mechanical properties of the aluminum alloy.
[0187] According to Table 1 in combination with Examples 1 and 7, and Comparative Examples 12 and 13, it can be seen that the heat-treatment-free high-strength and heat-resistant aluminum alloy provided by the present invention can obtain excellent mechanical properties by adopting a non-equilibrium rapid solidification molding method (such as laser powder bed molding, laser cladding molding), while the aluminum alloy obtained by traditional hot pressing molding or spark plasma sintering molding has poor mechanical properties.
[0188] This is because the non-equilibrium rapid solidification molding has a fast cooling speed, insufficient diffusion, large undercooling, short nucleus growth time, and no time for dendrites to grow, which can obtain the composition, phase structure and microstructure that cannot be obtained by conventional solidification. For Al-Ce-La alloys, conventional casting is easy to 11 The (Ce, La)3 phase is coarse and the strengthening effect is poor. In addition, the solid solubility of Ce and La in the matrix is extremely low, and it is impossible to further control the Al content through solid solution aging heat treatment. 11 The (Ce, La)3 phase can be refined and its distribution controlled during the solidification process through non-equilibrium rapid solidification to optimize the performance.
[0189] In summary, the heat-treatment-free high-strength and heat-resistant aluminum alloy provided by the present invention is formed by a specific alloy element design combined with a non-equilibrium rapid solidification forming method to optimize the microstructure of the alloy, thereby achieving excellent mechanical properties of the aluminum alloy at room temperature and medium and high temperature conditions; and the heat-treatment-free high-strength and heat-resistant aluminum alloy can be directly printed and formed, with a short process flow, high stability, and near-net forming. No subsequent machining or heat treatment is required, and it can be used to produce heat-resistant aluminum alloy structures with complex shapes, such as internal combustion engine cylinders, high-horsepower engine pistons, etc.
[0190] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A high-strength and heat-resistant aluminum alloy without heat treatment, characterized in that: In terms of mass percentage, it includes the following ingredients: Lanthanum-cerium mixed rare earth RE: 14~16%, silicon: 0.5~1%, molybdenum: 0.2~0.5%, titanium: 0.5~1%, chromium: 0.2~0.5%, the balance is aluminum and unavoidable impurities; Wherein, the contents of lanthanum and cerium in the lanthanum-cerium mixed rare earth RE are both 30-70%, and the contents of the remaining rare earth elements except lanthanum and cerium in the lanthanum-cerium mixed rare earth RE are ≤1%; The heat treatment-free high-strength and heat-resistant aluminum alloy is formed by melting metal powder through a non-equilibrium rapid solidification molding method, the metal powder includes Al-RE-Si alloy powder, molybdenum powder, titanium powder and chromium powder, and the Al-RE-Si alloy powder is made by a spray deposition gas atomization powder making process; the non-equilibrium rapid solidification molding method refers to the use of a high-energy density heat source to locally melt and rapidly solidify the metal powder.
2. The heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 1, characterized in that: The total content of molybdenum, titanium and chromium in the heat-treatment-free high-strength heat-resistant aluminum alloy is 1-1.5%.
3. The heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 1, characterized in that: The phase composition of the heat-treatment-free high-strength heat-resistant aluminum alloy includes α-Al phase and Al 11 (Ce, La)3 phase.
4. The heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 3, characterized in that: The Al 11 The (Ce, La)3 phase is distributed on the α-Al phase in the form of nano blocks and / or networks.
5. The heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 1, characterized in that: The density of the heat-treatment-free high-strength heat-resistant aluminum alloy is greater than 99%.
6. A method for preparing a heat-treatment-free high-strength heat-resistant aluminum alloy as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: Melting and pouring lanthanum-cerium mixed rare earth RE, aluminum and silicon to obtain a cast Al-RE-Si alloy; The cast Al-RE-Si alloy is spray-formed and atomized to form Al-RE-Si alloy powder; Mixing Al-RE-Si alloy powder, molybdenum powder, titanium powder and chromium powder to obtain mixed powder; The mixed powder is melt-formed by non-equilibrium rapid solidification forming method to obtain a high-strength and heat-resistant aluminum alloy without heat treatment.
7. The method for preparing a heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 6, characterized in that: The atomization temperature of the spray forming is 800-900° C., the atomization pressure is 5-10 MPa, and the atomization distance is 600-1000 mm.
8. The method for preparing a heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 6, characterized in that: The particle size distribution of the Al-RE-Si alloy powder is between 15 and 65 μm, and the average particle size is between 45 and 55 μm.
9. The method for preparing a heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 6, characterized in that: The mixed powder is melt-formed by non-equilibrium rapid solidification molding, specifically: Laser powder bed is used to melt and shape the mixed powder.
10. The method for preparing a heat-treatment-free high-strength heat-resistant aluminum alloy according to claim 9, characterized in that: The laser powder bed has a printing power of 220-300W, a scanning rate of 800-1200mm / s, and a laser volume energy density of 60-100J / mm 3 .
Citation Information
Patent Citations
Rapidly solidified aluminum-rare earth element alloy and method of making the same
US20180237893A1
High-strength heat-proof aluminum alloy material and producing method thereof
WO2011023060A1